Analisis Peran Konservasi Nilai Peduli Lingkungan Terhadap Penerapan Program SDGS Nomor 4 Pendidikan Bermutu - Pramesti, Rima Dian; T, Trimurtini (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Since its launch in 2000, the United Nations (UN) launched the MDGs program for the period 2000 to 2015. From 2016 to 2030, the UN launched the SDGs program again. As a member of the United Nations (UN), Indonesia together with 192 other countries is involved in implementing the SDGs as a sustainable development program. The Indonesian government has committed to achieving SDGs success through the policies stated in Presidential Regulation Number 59 of 2017. In this study the author focuses on the implementation of SDGs Number 4 related to quality education. The results of this research show that Conservation and Sustainable Development Goals: SDGs are a series of goals adopted by the UN to achieve sustainable development until 2030. These goals cover various aspects, such as poverty alleviation, health and welfare, quality education, clean water management, forest protection , and so forth. Conservation has an important role in achieving these goals by protecting and preserving natural resources necessary for sustainable development. That conservation relations have a strong relationship with achieving the SDGs. Conservation is not only about protecting nature, but also about maintaining the quality of human life. Through comprehensive environmental conservation efforts, we can achieve sustainable development goals and create a better world for future generations.